Control of cardiovascular responses to stress by CRF in the bed nucleus of stria terminalis is mediated by local NMDA/nNOS/sGC/PKG signaling - Oliveira, Leandro A. [UNESP]; Gomes-de-Souza, Lucas [UNESP]; Benini, Ricardo [UNESP]; Crestani, Carlos C. [UNESP] (Elsevier, 2018)
The aims of the present study were to assess an interaction of corticotropin-releasing factor (CRF) neurotransmission within the bed nucleus of the stria terminalis (BNST) with local nitrergic signaling, as well as to investigate an involvement of activation of local NMDA glutamate receptor and nitric oxide (NO) signaling in control of cardiovascular responses to acute restraint stress by BNST CRF neurotransmission in rats. We observed that CRF microinjection into the BNST increased local NO release during restraint stress. Furthermore, bilateral microinjection of CRF into the BNST enhanced both the arterial pressure and heart rate increases evoked by restraint stress, but without affecting the sympathetically-mediated cutaneous vasoconstriction. The facilitation of both pressor and tachycardiac responses to restraint stress evoked by BNST treatment with CRF were completely inhibited by local pretreatment with either the selective NMDA glutamate receptor antagonist LY235959, the selective neuronal nitric oxide synthase (nNOS) inhibitor Nω-Propyl-L-arginine (NPLA), the soluble guanylate cyclase (sGC) inhibitor 1H-[1,2,4]Oxadiazolo[4,3-a]quinoxalin-1-one (ODQ) or the protein kinase G (PKG) inhibitor KT5823. Taken together, these results provide evidence that BNST CRF neurotransmission facilitates local NMDA-mediated glutamatergic neurotransmission and activates nitrergic signaling, and this pathway is involved in control of cardiovascular responses to stress.
Keywords: Blood pressure; BNST; Corticotropin-releasing factor; Glutamate; Heart rate; Nitric oxide